Transformation of rural areas with high urban impact: the example of the largest cities in the Warmia and Mazury region - Szczepańska, Agnieszka; Wasilewicz-Pszczółkowska, Monika; Krzywnicka, Iwona; Senetra, Adam (International Conference “Environmental Engineering”, 2017)
The paper discusses rural transformations resulting from urban influences. The analyzed area consists of rural municipalities (the smallest administrative units in Poland) in the immediate vicinity of Olsztyn, Elbląg and Ełk – the largest cities in Warmia and Mazury. The type and rate of social and spatial changes in rural areas with high urban impact were analyzed. The following issues have been addressed: – a comparison between demographic changes in rural municipalities neighboring on urban centres and demographic changes in the city, – changes in the land use structure of rural municipalities neighboring on urban centers, with particular emphasis on open and protected spaces, – architectural changes in the analyzed suburban areas, – landscape changes in the analyzed suburban areas.